(untitled) (Ameghiniana, 2026)
X-ray computed microtomography was used to segment and re-describe the braincase of the juvenile specimen of Megaraptor namunhuaiquii, providing novel anatomical endocranial information. The reconstructed soft tissues include the brain, cranial nerves, blood vessels, inner ear, and pneumatic sinuses. Some structures of the braincase anatomy were re-interpreted, and the endocranial anatomy was compared with that of Murusraptor barrosaensis (the only other megaraptoran with studied endocranial anatomy) and more derived theropods. The braincase and the brain exhibit a mosaic of primitive and derived characters that support the previously proposed close relation of Megaraptor with basal coelurosaurian theropods (including basal Tyrannosauroidea). A high degree of braincase pneumaticity, a high mean range of hearing, and a relatively large floccular lobe of the cerebellum are features that suggest that Megaraptor was an agile bipedal predator compared to non-coelurosaur coeval theropods, such as abelisaurids. Its cognitive and sensorial abilities may have allowed Megaraptor to compete with coelurosaurs (unenlagiines?) or at least reach many of their hunting capabilities.